SLASH-IT LAZADA: ANALISIS PEMIKIRAN IBN TAIMIYAH DALAM KONSEP HARGA, HAK MILIK DAN PASAR - Moh. Holilur Rohman (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2022)
Online shopping experienced significant growth in Indonesia. The way to attract the attention of e-commerce users in online shopping is that interesting events are often held, starting from amazing discount promos to using vouchers, one of which is a promo to attract purchase interest is Slash-It. The Slash-it system in getting low prices on each item has conditions that depend on the desired product. The purpose of writing is to describe the practice of product purchasing, pricing and ownership rights using Slash-It in markets that are in accordance with Islamic teachings, and the authors refer to the thoughts of Imam Ibn Taimiyah in the concept of price, property rights and markets. This research is classified as a qualitative research library study or library research. The results of the discussion show that according to Ibnu Taymiyah, the price setting that is permissible and must be applied is if the price is not sold above the official price. In the practice of Slash It, according to Imam Ibn Taimyyah, this practice is not permissible because it raises speculative aspects in obtaining the item and deviates from the provisions of Islamic law. Keywords: Slash It; Price Concept; Ibn Taimiyah.